Sea Spots : Perzeption und Repräsentation maritimer Räume im Kontext englischer und niederländischer Explorationen um 1600 - Hilfiker, Franziska (Böhlau, 2019)
In the period around 1600, the rising navies of England and Holland made expeditions into distant waters of the Arctic and the Sudsee, or attempted to sail around the world via Magellan Strait. The sea and ship became contact zones as well as places of imagination and knowledge production. The exploration trips of the European maritime industry around 1600 produced a wealth of texts, images and cartographic works in which the experience and perception of the besgeded areas as well as conceptions were processed. In her book, the author argues that not only were terrestrial and insular destinations of travel recorded and recorded, in particular, new maritime spaces with their own individual qualities were included in the treasures of imagination and the contemporary body of knowledge. In the context of colonial competitions between existing and emerging maritime powers, effective maritime spaces of meaning - sea spots - were created, through which claims, identity, fear and power were debated and negotiated. The author negotiates the sea as a differentiated, mosaic-like space consisting of a dot grid (in fact as well as imagined and projected) imperial presence, thus illustrating the importance of maritime spaces in the context of early modern expansion.